2021
DOI: 10.2166/washdev.2021.184
|View full text |Cite
|
Sign up to set email alerts
|

In situ treatment technologies for pit latrines to mitigate groundwater contamination by fecal pathogens: a review of recent technical advances

Abstract: On-site sanitation systems such as pit latrines are extensively used around the world, while there is a growing number of evidence documenting the impact of pit latrines on groundwater quality that may affect human health. Hence, this paper summarizes the various safe-sanitation technologies by broadly categorizing them into fecal pathogen disinfection methods (anaerobic digestion, chemical disinfection, biological additives, solar pasteurization and vermicomposting) and capturing methods (pit lining and perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…This study aimed to determine the alkali dosage and contact time required for virus inactivation in faecal sludge and wastewater with high solid loading. Since alkaline treatment is widely used for sludge treatment, we identified several reviews aimed at evaluating the pathogen inactivation efficacy of alkaline treatment (e.g., (57)(58)(59)). However, previous reviews have provided little quantitative data on viruses and bacteriophage.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to determine the alkali dosage and contact time required for virus inactivation in faecal sludge and wastewater with high solid loading. Since alkaline treatment is widely used for sludge treatment, we identified several reviews aimed at evaluating the pathogen inactivation efficacy of alkaline treatment (e.g., (57)(58)(59)). However, previous reviews have provided little quantitative data on viruses and bacteriophage.…”
Section: Discussionmentioning
confidence: 99%
“…Pit-latrines are assumed to be not being emptied, based on estimates that approximately 1% of pit-latrines are undergoing emptying in Malawi (Hinton et al, 2024). Similarly, pit-latrines were assumed to be unlined, around 10-15% of pit-latrines are estimated to be lined nationally (Chiposa et al, 2017, Hinton et al, 2024, where lining is used, interwoven logs and bamboo sticks are commonplace and can provide limited capacity to minimise contamination (Namwebe et al, n.d;Saxena and Den, 2022). Assumptions regarding lining and emptying of pit-latrines are therefore deemed to be justified.…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…The result showed that the turbidity of all the well water sampled is not within the permissible limits of 5 NTU except in January 2021 (SON, 2007;WHO, 2014;. The measurement of pH is one of the most frequently used tests in water chemistry (Saxena, 2021). In Figure 5, the mean seasonal pH variation was recorded to be highest in September during rainy season) at 7.5 and lowest in January during dry season at 7.3.…”
Section: ) Statistical Analysesmentioning
confidence: 96%
“…Studies also showed that shallow wells, being a relatively more costeffective and accessible source of water for an average household in developing countries, including Nigeria are frequently used without regard for their potability. This is attributed as the consumption of untreated water source, thus, a cause of waterborne diseases (Ale et al, 2015;Malla et al, 2018;Ogeleka & Emegha, 2021;Saxena, 2021). Fagerli et al (2017); Pal et al (2018); Adnani et al (2020); Bastaraud et al (2020) and Afolabi et al (2021) strongly viewed that the prevalence of gastrointestinal diseases (such as cholera, diarrhoea, dysentery typhoid and viral hepatitis) is caused by consumption of contaminated water.…”
Section: Introductionmentioning
confidence: 99%